Academic Policy of Islamic Private University as Response to the Challenges of Disruption Era - Laily Hidayat; Fakhruddin Fakhruddin; Arief Yulianto; Titi Prihatin (Universitas Negeri Semarang, 2021)
Some of the functions of education policy research in general are: 1) providing services in the form of facts (evidence), input that is affirmative verification as a refinement for all stages in the policy research process, 2) providing criticism in the form of perspectives, falsifying alternatives or constructive criticism of improving the quality of education policy through policy formulation, 3) facilitating policy makers in formulating policy designs, by providing arguments or information they need in solving fundamental educational problems. This study aims to see descriptively and analyze the response of private universities' academic policies to the development of the era of disruption that has hit all lines of people's lives, including universities. This response is absolutely necessary to show the readiness and existence of private universities in their role as agents that contribute to the intellectual life of the nation and prepare human resources who are strong and can adapt in this era that is changing soo fast. This research uses a single case study research design. This study found that private Islamic religious universities have shown certain responses to the development of the era of disruption in the form of completely new academic policies from previous policies, which is very visible as a response to the demands of the digital era and the industrial era 4.0. The responses include academic policies in the fields of education, research, and community service, which can be seen in detail in the review of this research report.